THE ISLAMIC VIEW TOWARD PEOPLE WITH DISABILITIES IN EDUCATION POLICY IN INDONESIA - Gustiana Yuantini (Sunan Kalijaga International Journal on Islamic Educational Research, 2019)
Abstract: Islam views a person before Allah. It is not because of the physical, but the taqs. Thus, individual has equal rights and obligations in this case, education. Along with the statements within Statute Number 20 in 2003, it stated that "every citizen has the same right to obtain good quality of education." It is understandable that every citizen can obtain an education and without exception, including those with disabilities. Through the library research method derived from books, laws and research journals, this paper describes how Islam views toward people with disabilities in education policy in Indonesia. Based on this study, it is well known that in Islam the human standing before God is the same as the person of disability who differentiates only his faith and his taqs. Education in Islam is a human right and duty. Education in Indonesia is policy that regulates education for those with disabilities.